To ingest or rest? Specialized roles of lateral hypothalamic area neurons in coordinating energy balance - Brown, Juliette A.; Woodworth, Hillary L.; Leinninger, Gina M. (Frontiers in Systems Neuroscience, 2015)
Survival depends on an organism’s ability to sense nutrient status and accordingly regulate intake and energy expenditure behaviors. Uncoupling of energy sensing and behavior, however, underlies energy balance disorders such as anorexia or obesity. The hypothalamus regulates energy balance, and in particular the lateral hypothalamic area (LHA) is poised to coordinate peripheral cues of energy status and behaviors that impact weight, such as drinking, locomotor behavior, arousal/sleep and autonomic output. There are several populations of LHA neurons that are defined by their neuropeptide content and contribute to energy balance. LHA neurons that express the neuropeptides melanin-concentrating hormone (MCH) or orexins/hypocretins (OX) are best characterized and these neurons play important roles in regulating ingestion, arousal, locomotor behavior and autonomic function via distinct neuronal circuits. Recently, another population of LHA neurons containing the neuropeptide Neurotensin (Nts) has been implicated in coordinating anorectic stimuli and behavior to regulate hydration and energy balance. Understanding the specific roles of MCH, OX and Nts neurons in harmonizing energy sensing and behavior thus has the potential to inform pharmacological strategies to modify behaviors and treat energy balance disorders.